The Practicality of AsarFonts for Islamic and Arabic Studies - Abd Jalil, Borham; Asar, Abdul Karim; Kamaruzaman, Jusoff; Azwin Arif, Abdul Rahim; Mohammad Musab, Azmat Ali; Nor Yazi, Khamis; Mohammad Affendy, Omardin (IDOSI Publications, 2011)
Most of todayâs writing tools are designed to accommodate multiple language features in a single document; unfortunately the features are not thoroughly implemented in Islamic and Arabic studies. This paper proposes a solution to overcome such problem by the invention of AsarFonts. It is a single font set that consists of some standard fonts that are used in the studies. The fonts are Times New Roman font with all standard Arabic Romanization letters and Traditional Arabic font with additional of six JÄwÄ« letters. AsarFonts also comes with English -Arabic Romanization keyboard layout namely as AsarEN and Arabic-JÄwÄ« QWERTY keyboard layout known as AsarAR; both are the first in the world. Through the invention of AsarFonts, the complicated process in writing academic articles in Islamic and Arabic studies should be eliminated, or at least it can be reduced to a minimum level.